Substitution Reaction of Palladium (II) Complexes With Some Amino Acids - Aisha B. A. Elmagtof; Afaf M. A. Elmagtof (المجلة الأفروآسيوية للبحث العلمي, 2024)
A new set of palladium (II) complexes with sodium salts of the following amino acids have been investigated: L-arginine (argH), L-serine (serH2), L-glutamic acid (gluH2), L-glutamine (glnH), L-asparagine (asnH) and L- threonine (thrH2). The isolated complexes have been characterized by their elemental analyses, solubility, conductivity measurements, IR, electronic absorption and 13C-NMR spectra.